The Modal Status of Kant's Postulate of God's Existence - (:unkn) unknown (My University, 2013)
Kant is traditionally read as arguing that moral agents are rationally required to postulate the actual existence of God, but contemporary commentators' reconstructions of the argument only seem sufficient to warrant postulating the merely possible existence of God. There have been three attempts to address this seeming lacuna between what the argument is supposed to justify and what it does justify. Allen Wood defends the traditional interpretation - that Kant postulated the actual existence of God. M Jamie Ferreira proposes a revisionary interpretation - that Kant postulated the possible existence of God. Finally, Paul Guyer simply criticizes Kant for postulating the actual existence of God when his argument only justifies postulating the possible existence of God. I argue that Allen Wood's defense is insufficient to ground the appropriate propositional attitude toward the postulates while M Jamie Ferreira's proposal cannot pass as a reading of Kant. Nonetheless, I argue that Kant need not be criticized because the seeming lacuna does not arise if we are sufficiently sensitive to the modality of the judgment Kant takes to be required for rational pursuit of the highest good.
Keywords: Belief; God; Kant; Modal; Possibility; Postulate